Derivative Words Scraping of Every Quranic Root Word from the Quran Corpus Web using Python to Support the Quranpedia Project - Idzhari Syaeful Ma'mun -; Eko Darwiyanto; Moch. Arif Bijaksana (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The Qur'an, as a guide to life for Muslims, has given birth to various disciplines such as tafsir science, fiqh science, hadith science, nahwu science, and balaghah science. However, the limited number of websites on learning and understanding the Qur'an is a problem that can hinder Muslims from exploring the contents of the Qur'an. To overcome this problem, the Quranpedia project was initiated. Quranpedia is a web-based application designed to resemble Wikipedia in providing in-depth explanations of derivative words in the Qur'an. Using the "Scraping" technique, Quranpedia collects data from various sources to provide a comprehensive explanation of nouns in the Qur'an and Hadith. One of the main challenges in this project was to find the common root of nouns in the Qur'an and hadith. To overcome this challenge, a method was used to transform words from sentences to their root words. Thus, Quranpedia can have the ability to look up the root word of a noun. This allows users to have a better understanding of derivative words in the Qur'?n and how they are used in different contexts. The objective of this research is to create a derivative word scraping program that scrapes all derivative words in the Quran from the Corpus Quran web accurately. The problem discussed in this research covers both how one can scrape derivative words of each root word in the Quran from the Corpus Quran web and whether the data scraped from the web is complete and accurate. The method to ensure that these problems are solved includes using the Python programming language to create the program and then testing the program itself. The interim results achieved is whether the data is complete or not